Pitfalls and limitations in Group 6 triamidophosphane chemistry: cage-closure restrictions in square-pyramidal nitrido complexes and degradation via spiro-[4.4]-[lambda]5-amidophosphorane formation - Sietzen, Malte; Batke, Sonja; Merz, Lukas; Wadepohl, Hubert; Ballmann, Joachim (European journal of inorganic chemistry, 2017)
The benzylene-linked triaminophosphanes P(C6H4-o-CH2NHXyl)3 ([A]H3) and P(CH2C6H4-o-NHPh)3 ([B]H3) react with (Me2N)3Mo≡N to afford the square-pyramidal nitrido complexes 1 and 2, each comprising one residual dimethylamido moiety and one uncoordinated ligand sidearm. Only the [A]-coordinated complex 1 was found to eliminate the remaining dimethylamido ligand on heating. Instead of the closed-cage molybdenum(VI) nitrido complex [A]Mo≡N, cyclometalated molybdaziridine 3 was isolated, as the syn alignment of the uncoordinated sidearm and nitrido ligand in 1 inhibits a productive cage-closure reaction. By using [NPN]-coordinated model complexes, analogous syn arrangements were found not only for molybdenum, but also for the related tungsten nitrido complexes and the group 5 imides. Attempts to access the closed-cage MoVI nitrido comlex [A]Mo≡N by transmetalation between [A]Sn(nBu) (9) and (tBuO)3Mo≡N led to the formation of spiro-[4.4]-λ5-amidophosphorane 10. These results contrast with the findings made for azatranes and methylene-linked exo-P-configured triamidophosphane complexes.